Literatura e dança: rastros de um diálogo e sua manifestação em Mallarmé, Valéry e Nijinsky - Roberta Kelly Paiva (2016)
This thesis presents a study on the dialogue between literature and dance departing from a critical review of philosophical and literary texts as well as of a choreographic work. It is sustained the hypothesis that choreographic art, not yet being under sufficient scrutiny in the tradition of literary comparativism, has its place attested in the history of aesthetic and literary thinking, so deserving more attention in this field of investigation that comprehends literature in its connection with the other arts. Divided in two parts, the thesis brings first a critical approach of texts by ancient writers such as Plato, Aristotle and Lucian, as well as by an illuminist, Jean- -Georges Noverre. In the second part, the analysed corpus constitutes of some texts by the French poets Stéphane Mallarmé and Paul Valéry and, besides, of a ballet by a dancer and choreographer of Diaghilevs Ballets Russes, Vaslav Nijinsky. The main discussion lays on the concept that those authors bring about dance in some of their texts and, in the case of the choreographic work, the discussion is concerned to the analysis of this ballet in its relation specially with literature. In the light of such an approach, our conclusion is that dance is a legitimate part in the dialogues ever established between literature and the arts, and that its inclusion among the research dedicated to to the analysis of such dialogues proves itself to be of potential fecundity to the very development of comparative literary studies.